The Impact of Immigration on the Wage Distribution in Switzerland - Sandro Favre (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2011)
Recent immigrants in Switzerland are overrepresented at the top of the wage distribution in high and at the bottom in low skill occupations. Basic economic theory thus suggests that immigration has led to a compression of the wage distribution in the former group and to an expansion in the latter. The data confirm this proposition for high skill occupations, but reveal effects close to zero for low skill occupations. While the estimated wage effects are of considerable magnitude at the tails of the wage distribution in high skill occupations, the effects on overall inequality are shown to be negligible.
Keywords: F22; J31; J61; 330; Immigration; Wage Distribution; Occupation Groups; Inequality